2018
DOI: 10.3390/su10103825
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming Improves Soil Microbial Abundance and Diversity under Greenhouse Condition: A Case Study in Shanghai (Eastern China)

Abstract: Agricultural practices have significant impacts on soil properties and microbial communities; however, little is known about their responses to open field and plastic tunnels under organic and conventional farming. We therefore investigated the responses of soil chemical variables and microbial communities to different agricultural management and cultivation types, including organic management in open field (OF), organic management in plastic tunnels (OP), conventional management in open field (CF) and convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
5
23
0
2
Order By: Relevance
“…In another study [107], the long-term effects of organic versus conventional fertilization on soil microbial communities were investigated, finding out that the former modulated microbial community composition while increasing microbial richness and diversity. Similarly, other authors [108] reported that organic farming promotes soil microbial diversity and the abundance of beneficial soil microorganisms, with concomitant beneficial effects on the stability of the soil ecosystem. An improvement in soil microbial structural and functional diversity, as well as an increase in bacterial richness and evenness, was reported [109] after the application of organic amendments to agricultural soil.…”
Section: Beneficial Effects Of Organic Amendmentsmentioning
confidence: 58%
See 1 more Smart Citation
“…In another study [107], the long-term effects of organic versus conventional fertilization on soil microbial communities were investigated, finding out that the former modulated microbial community composition while increasing microbial richness and diversity. Similarly, other authors [108] reported that organic farming promotes soil microbial diversity and the abundance of beneficial soil microorganisms, with concomitant beneficial effects on the stability of the soil ecosystem. An improvement in soil microbial structural and functional diversity, as well as an increase in bacterial richness and evenness, was reported [109] after the application of organic amendments to agricultural soil.…”
Section: Beneficial Effects Of Organic Amendmentsmentioning
confidence: 58%
“…In addition to improving soil biological properties, organic amendments are also known to positively influence soil chemical properties. In fact, the abovementioned positive effects of organic amendments on soil microbial communities are often linked to changes in soil chemical characteristics driven by the application of amendments [45,108,120]. Several authors [121,122] evidenced the key role of soil pH for both microbial community structure and function.…”
Section: Beneficial Effects Of Organic Amendmentsmentioning
confidence: 99%
“…It is true that GI is currently emerging by becoming an interesting tool for cost-effective urban sustainability [8][9][10][11][12][13][14][15][16][17][18][19][20], and for this reason it is seen in the framework of the present paper as a main point of this case study in terms of innovative architectural programmatic regeneration and applied thermal engineering investigation. Additionally, as it results from Taylor Lovell's research [20] it is argued that the contemporary Occidental world employs urban agriculture as a new boundary for land use planning, architectural, and landscape design in order to follow "a sustainable urban development and transformation of the cityscape supporting community farms, allotment gardens, rooftop gardening, edible landscaping, urban forests, and other productive features of the urban environment" [20].…”
Section: Coupling Urban Agriculture To Thermodynamic Architectural Dementioning
confidence: 99%
“…As a consequence, a variety of economic-environmental multifaceted reforms are applied in an international level so as to "experiment with urban and peri-urban economic bases which make the city the center of transition towards a 'low carbon' economy" [1]. Since the early 1970s, the first petrol crisis of 1973, architecture-and the building sector in general-became a target of environmental reform [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This reform resulted in segregating disciplines and creating antagonist relations.…”
Section: Introduction and General Contextmentioning
confidence: 99%
See 1 more Smart Citation